1941
DOI: 10.5962/bhl.title.8323
|View full text |Cite
|
Sign up to set email alerts
|

The families and genera of living rodents / by J.R. Ellerman ; with a list of named forms (1758-1936) by R.W. Hayman and G.W.C.Holt.

Abstract: Geographical Distribution. -Throughout the Holarctic, Indo-Malayan, Australasian, African and Neotropical regions, from Arctic regions of Eurasia south to the Cape of Good Hope, and Tasmania; east to Fiji and other islands of the Pacific; Madagascar; and in the New World from Arctic regions including Greenland south to Tierra del Fuego, and including the Galapagos Islands. Number of Genera. -I have examined and retained one hundred and eight)'-six genera, divided among twelve subfamilies. At least six, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

1948
1948
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 0 publications
1
34
1
Order By: Relevance
“…Howell (1929) expanded the two-genus model by further dividing Eutamias into two subgenera, Eutamias (T. sibiricus) and Neotamias (western North American species). Ellerman (1940) in his study of rodent genera did not accept Eutamias as a valid genus, because he did not consider the characters used to elevate it to a generic rank to be phylogenetically informative. These characters include the presence/absence of the P3 upper premolar, which Ellerman pointed out were previously shown to have no importance in demonstrating evolutionary relationships.…”
Section: Generic Debates the Geographic Distribution Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…Howell (1929) expanded the two-genus model by further dividing Eutamias into two subgenera, Eutamias (T. sibiricus) and Neotamias (western North American species). Ellerman (1940) in his study of rodent genera did not accept Eutamias as a valid genus, because he did not consider the characters used to elevate it to a generic rank to be phylogenetically informative. These characters include the presence/absence of the P3 upper premolar, which Ellerman pointed out were previously shown to have no importance in demonstrating evolutionary relationships.…”
Section: Generic Debates the Geographic Distribution Ofmentioning
confidence: 99%
“…These characters include the presence/absence of the P3 upper premolar, which Ellerman pointed out were previously shown to have no importance in demonstrating evolutionary relationships. Ellerman (1940) suggested that color pattern is too influenced by the environment and that geographical distribution is not an acceptable phylogenetic character. Bryant (1945) examined this taxonomic question on the basis of fossil evidence.…”
Section: Generic Debates the Geographic Distribution Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other Rattus, it exhibits an intriguing mosaic of both 'archaic' traits (see Aplin, Chesser & ten Have, 2003) and highly-derived features, the latter including the unique configuration of the palate (Thomas, 1922;Ellerman, 1941). In all known specimens, head and body length measures 118-135 mm (n = 3), tail length 126-140 mm (n = 4), hindfoot length 28-30 mm (n = 4), ear length 17-18 mm (n = 4), and weight 66.5 g (n = 1).…”
Section: Rattus Feliceus Thomas 1920mentioning
confidence: 99%